Райский остров: роман / Д. Барнет ; пер. с англ. Е. Г. Шабаловой - Барнет Джилл (Шарм, 2003)
Экземпляры: ф.3 (2005) / Инвентарный номер: 48752 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Б 25 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)